Pemberdayaan Ekonomi Petani Pasca Bencana Berbasis Inovasi Sosial Melalui Sociopreneur di Desa Supiturang Kabupaten Lumajang - Hijri, Yana Syafriyana; Sulistyono, Setyo Wahyu; Kurniawan, Wahyudi; Salam, Abdus (Abdimas Indonesian Journal, 2024)
The economic empowerment of farmers in disaster-affected areas or survivors is certainly a problem in the post-disaster phase during rehabilitation and reconstruction, one of which is the economic sustainability of the community so that they can still return to the new normal life. This is what happened in Supiturang Village, Pronojiwo District, where after the eruption of Mount Semeru, many residents lost their jobs, agricultural production decreased, including psychological conditions due to the trauma of the earthquake disaster. Social innovation as "new ideas that successfully achieve social goals, emerging in various forms, including technological innovation, process innovation, and organizational innovation, often arise from collaboration between various stakeholders, such as NGOs, governments, community groups, and companies that lead to holistic and sustainable solutions to complex social problems (1) increasing capacity, well-being and increasing sustainability opportunities. Sedankan sociopreneur (social entrepreneurship) combines social empowerment and entrepreneurship, becoming an alternative in reducing social and economic problems, such as unemployment, economy, education, gender, health, including disaster problems. (2) Community service in Supiturang Village after the eruption of Mount Semeru was carried out using a participatory method based on social innovation which aims to restore and develop the local economy in a sustainable manner. Through collaboration with various stakeholders, the program not only focuses on strengthening economic capacity, but also on the development of social and institutional aspects, so that the interventions provided can be more targeted and relevant to local conditions. With an integrated approach to overcome the challenges faced after the eruption of Mount Semeru, through several solutions, including: strengthening agricultural production innovation, diversifying agricultural products with a sociopreneur approach through the added value of agricultural product processing, including increasing farmers' income and competitiveness with technology through  a digital marketplace based on local wisdom) independent, progressive and sustainable.